Phytochemical composition and antioxidant activities of Dianthus Thunbergii Hooper and Hypoxis Argentea Harv Ex Baker: Plants used for the management of Diabetes Mellitus in Eastern Cape, South Africa (2018)
Background: Inhabitants of the Eastern Cape Province of South Africa use the roots of Dianthus thunbergii and corms of Hypoxis argentea to treat diabetes mellitus and other ailments. Objective: The objective of this study was to analyze the phytochemical composition and antioxidant activities of the aqueous and ethanol extracts of the roots and corms of two plants. Materials and Methods: Total phenolics, flavonoids, flavonols, proanthocyanidins, tannins, and alkaloids were determined by standard methods. The scavenging activities of the extracts against 1,1 diphenyl 2 picrylhydrazyl (DPPH), 2’ azino bis (3 ethylbenthiazoline 6 sulfonic acid (ABTS), nitric oxide (NO), hydrogen peroxide (H2 O2 ), and their ferric reducing antioxidant potentials (FRAPs) were measured. Results: The ethanol extract of H. argentea had the highest content of phenolics (66.71 ± 2.71 mg gallic acid equivalent/g) and tannins (1.18 ± 0.07 mg TAE/g), while the ethanol extract of D. thunbergii gave higher contents of flavonoids and proanthocyanidins (62.21 ± 1.75 mg Qe/g and 432.62 ± 2.43 mg Ca/g, respectively). Flavonols were the most predominant in the aqueous extract of H. argentea (25.51 ± 1.92 mg Qe/g). We observed a concentration dependent response in the ABTS and H2 O2 scavenging activities and FRAP values of the extracts and standards (Vitamin C, butylated hydroxytoluene, and rutin). The ethanol extracts of both plants generally demonstrated better antioxidant activities against H2O2 , NO, and ABTS while also possessing better reducing power than the aqueous extracts. The aqueous extract of D. thunbergii, however, showed the best DPPH scavenging activity. Conclusion: The higher content of phytochemicals and antioxidant capacity obtained for the ethanol extracts of D. thunbergii and H. argentea may prove to be valuable information in selecting suitable extraction solvents for the medicinal applications of both plants.